Elevated level of fibrinogen increases caveolae formation; Role of matrix metalloproteinase-9 - Muradashvili, Nino (2014)
The role of the inflammatory agent fibrinogen (Fg) in increased pial venular permeability has been shown previously. It was suggested that an activation of matrix metalloproteinase-9 (MMP-9) is involved in Fg-induced enhanced transcytosis through endothelial cells. However, direct link between Fg, caveolae formation, and MMP-9 activity has never been shown. We hypothesized that at an elevated level, Fg enhances formation of functional caveolae through activation of MMP-9. Male wild-type (WT, C57BL/6J) or MMP-9 gene knockout (MMP9−/−) mice were infused with Fg (4 mg/ml, final blood concentration) or equal volume of phosphate buffered saline (PBS). After 2 hours, mice were sacrificed and brains were collected for immunohistochemical analyses. Mouse brain endothelial cells were treated with 4 mg/ml of Fg or PBS in the presence or absence of MMP-9 activity inhibitor, tissue inhibitor of metalloproteinases-4 (TIMP-4, 12 ng/ml). Formation of functional caveolae was assessed by confocal microscopy. Fg-induced increased formation of caveolae, which was defined by an increased co-localization of caveolin-1 (Cav-1) and plasmalemmal vesicle-associated protein-1 (PV-1) and was associated with an increased phosphorylation of Cav-1, was ameliorated in the presence of TIMP-4. These results suggest that at high levels, Fg enhances formation of functional caveolae that may involve Cav-1 signaling and MMP-9 activation.